2005
DOI: 10.1142/s0219519405001291
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study on the Relationship Between Blood Circulation and Peripheral Temperature

Abstract: Computational simulation of the thermal transport phenomena in the human body has recently aroused a great deal of interest among researchers, because it can be applied in different areas such as medicine, rehabilitation, space suits, and others. In this study, we developed a coupling model to analyze the temperature distribution of the human middle finger. Firstly, a one-dimensional thermo-fluid model of blood circulation in the human upper limb is constructed. Secondly, a two-dimensional thermal model of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…When using the thermal images for heart rate detection, the blood system circulation causes a thermal change during periodic heartbeat, which can cause a corresponding change in the pixel value of the face, there by reflecting the heart rate information 7 . Thermal infrared video heart rate detection was first measured by professors Marc Garbey and others at the University of Houston Proposed in 2007, he uses adaptive filtering and fast Fourier transforms to measure human heart rate 8 .…”
Section: Heart Rate Signal Monitoring Algorithmmentioning
confidence: 99%
“…When using the thermal images for heart rate detection, the blood system circulation causes a thermal change during periodic heartbeat, which can cause a corresponding change in the pixel value of the face, there by reflecting the heart rate information 7 . Thermal infrared video heart rate detection was first measured by professors Marc Garbey and others at the University of Houston Proposed in 2007, he uses adaptive filtering and fast Fourier transforms to measure human heart rate 8 .…”
Section: Heart Rate Signal Monitoring Algorithmmentioning
confidence: 99%
“…He et al have developed a coupling model to analyze the temperature distribution of the human middle finger and observed that there was a periodic variation in skin temperature near the blood vessels [6]. Shao et al have generated hexahedron mesh of human hand from a series of sectional MR images and then simulated the heat transfer in hand based on porous media theory using FE model [7].…”
Section: Introductionmentioning
confidence: 99%